Expression of Erythroid Progenitor Cells and Erythrocytes on Dexamethasone Induced-Mice - Putra, Wira Eka; Soewondo, Aris (Biotropika: Journal of Tropical Biology, 2015)
Dexamethasone (Dex) is synthetic corticosteroid, known as anti-inflamation drug to ameliorate autoimmune diseases. It worked by inhibiting production of proinflamatory citokines. The aim of this experiment was to confirm the effect of administration of Dex on erythroid progenitor cells, TER-119+VLA-4+ and erythrocytes, TER-119+VLA-4- expression from bone marrow compartments. Two weeks old BALB/c mice were used and grouped into 3 injection treatments of Dex with six replications i.e. no injection (control), 0.5 mg/kg BW (dose 1), 10 mg/kg BW (dose 2). To investigate the therapeutic effect of dexamethasone, the mice were sacrified on day-7. The bone marrow cells were isolated and analyzed by flow cytometry. Data analysis was confirmed with the Kruskal-Wallis test followed by Mann-Whitney test with significance level (Î±) of 0.05. The result showed that administration of Dex on BALB/c mice increase the expression of erythroid progenitor cells, TER-119+ VLA-4+ and erythrocytes, TER-119+VLA-4- from bone marrow.Key words: Dex, erythrocytes, erythroid progenitor cells